* * * * * * * * * * * * * * * * * * * * *
ответ: 4) 15 ; 5) a₁ = -14 , d=3 или a₁ =2, d=3 ; 7) 30 c .
Объяснение:
4) 6x -5= ( (2x+1) +(9x+3) ) /2 ⇔12x -10 =11x + 4 ⇔ 12x -11x= 4+10 ⇒ x=15.
5) { a₄ - a₂ = 6 ; a₂*a₄= 55. ⇔{ (a₁+3d) - (a₁+d)=6 ; (a₁+3d) *(a₁+d)=55⇔
{ 2d=6 ; (a₁+3d) *(a₁+d)=55 ⇔{ d=3 ; (a₁+3*3) *(a₁+3)=55 ⇔
{ d=3 ; (a₁+9) *(a₁+3)=55. ⇔{ d=3 ; a₁² +4a₁ -28= 0⇔{ d=3 ; [a₁=2 a₁² +4a₁ -28= a₁² +4a₁ -28= 0 ⇒ [ a₁ = -14 ; a₁ =2 .
7). a₁=4,9 (м) ; d = 9,8 (м) ; S = 4410 (м)
S =(2a₁+ (n -1)d) *n/2
4410 =(2*4,9 +(n-1)*9,8 ) *n/2⇔ 4410 =4,9*n² ⇔n²=44100/49 = 900 ⇒
n =30 (с) .
х/2+у/3=3 умножим на 2 : х+у*2/3=6 (1)
х/3+у/2=1/3 умножим на 3 : х+у*3/2=1 (2)
вычитаем (2) из (1)
х+у*2/3 - (x+y*3/2) = 6 -1
у*2/3 - y*3/2 = 5
y (2/3 - 3/2) = 5
y = - 6
из (1) х+(-6)*2/3=6 ; x -2*2 = 6 ; x = 10
ответ (10; -6)
б)
х/3+у/2=5 умножаем на 15 : 5x +y * 15/2 = 75 (1)
5х-11у=1 (2)
вычитаем (2) из (1)
5x +y * 15/2 - (5x -11y)= 75 - 1
y * 15/2 +11y= 74
y (15/2 +11) = 74
y =4
из (2) считаем х
5х-11*4=1
5x = 45
x = 9
ответ (9; 4)